The textual framework and the reiteration of the western sight tradition in “PICTURE WINDOWS” series - Robles de la Pava, Juliana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2016)
The relevance of the representative tradition gets highlighted with a number of productions in the world of visual culture, demanding an analysis that question the own statute and condition of possibility of those images. The series of photographs by John Pfahl "PICTURE WINDOWS" proposes, from this analysis, an approach to the so-called scopic regime, referencing its inevitable link with visual memory constituted within the history of Western art. It is a possible way to revisit the narrative of Naturalism that has remained in a diversity of productive ways fell across by new types of images.